Bank Reform and Bank Efficiency in Pakistan. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Pakistan undertook major financial sector reforms starting in the late 1980s. The effects of these reforms on the profitability and cost and revenue efficiency of the banking sector are evaluated. The revenue performance of all banks, and especially the privatized banks, improved significantly, although costs also rose and relative performance across banks did not converge.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet